2000
DOI: 10.1002/cjce.5450780428
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pressure and impingement angle in flaming processes

Abstract: urbulent jets impinging on plane surfaces are used extensively in the process industries to achieve intense heating, cooling or T drying rates. Examples can be drawn from the drying and blasting processes, from glass melting, from metal cutting and forming, from fire testing of building materials, from oxy-flame and bonding applications, etc.The isothermal velocity field and the overall heat and mass transfer performance of jet impingement flows have been experimentally and computationally examined by several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Therefore, it is expected that the -RNG model gives better results in the regions of the flow where the mean strain rates are high. The performance of the -RNG model of turbulence has been investigated by Knowles and Saddington [11], Gordeev et al [12], Sharif and Mothe [13], Fernández et al [14], Chen [15], Liakos et al [16,17] and Sharif and Mothe [18] in jet flows and all confirmed that the -RNG model can be successfully used to model this type of flows. The -RNG model is numerically robust and faster than the triple transport model and has minimum turn-over time requirements for the calculations [17].…”
Section: Cfd Modeling Strategy Turbulence Model and Numericalmentioning
confidence: 72%
“…Therefore, it is expected that the -RNG model gives better results in the regions of the flow where the mean strain rates are high. The performance of the -RNG model of turbulence has been investigated by Knowles and Saddington [11], Gordeev et al [12], Sharif and Mothe [13], Fernández et al [14], Chen [15], Liakos et al [16,17] and Sharif and Mothe [18] in jet flows and all confirmed that the -RNG model can be successfully used to model this type of flows. The -RNG model is numerically robust and faster than the triple transport model and has minimum turn-over time requirements for the calculations [17].…”
Section: Cfd Modeling Strategy Turbulence Model and Numericalmentioning
confidence: 72%
“…They can therefore be applied in this flow where no previous computational experience exists. In general, details of turbulence characteristics can be captured only after careful selection and implementation of an appropriate turbulence model (Liakos et al, 2000a, b). Modified turbulence models (such as modified k –ε models; nonlinear k –ε models; low‐Reynolds number models; algebraic models of two, three, or more equations) show their numerical superiority over the standard k –ε, only in specific geometries, and should be implemented on a case‐to‐case basis.…”
Section: Introductionmentioning
confidence: 99%